High-field MRI reveals a drastic increase of hypoxia-induced microhemorrhages upon tissue reoxygenation in the mouse brain with strong predominance in the olfactory bulb - Hoffmann, Angelika; Kunze, Reiner; Milford, David; Heiland, Sabine; Bendszus, Martin; Pham, Mirko; Marti, Hugo; Helluy, Xavier (PLOS ONE, 2016)
Human pathophysiology of high altitude hypoxic brain injury is not well understood and research on the underlying mechanisms is hampered by the lack of well-characterized animal models. In this study, we explored the evolution of brain injury by magnetic resonance imaging (MRI) and histological methods in mice exposed to normobaric hypoxia at 8% oxygen for 48 hours followed by rapid reoxygenation and incubation for further 24 h under normoxic conditions. T2*-, diffusion-weighted and T2-relaxometry MRI was performed before exposure, immediately after 48 hours of hypoxia and 24 hours after reoxygenation. Cerebral microhemorrhages, previously described in humans suffering from severe high altitude cerebral edema, were also detected in mice upon hypoxia-reoxygenation with a strong region-specific clustering in the olfactory bulb, and to a lesser extent, in the basal ganglia and cerebral white matter. The number of microhemorrhages determined immediately after hypoxia was low, but strongly increased 24 hours upon onset of reoxygenation. Histologically verified microhemorrhages were exclusively located around cerebral microvessels with disrupted interendothelial tight junction protein ZO-1. In contrast, quantitative T2 and apparent-diffusion-coefficient values immediately after hypoxia and after 24 hours of reoxygenation did not show any region-specific alteration, consistent with subtle multifocal but not with regional or global brain edema.
Gesehen am 20.11.2019